Prevalence of Obesity and Predictive Section Value of Central Obesity among Medical Doctors to Diagnose Hypertension - Tamaraemumoemi Emmanuella Okoro (Journal of Clinical and Diagnostic Research, 2021)
Introduction: Central obesity has been shown to have worse health outcomes than general obesity and plays a greater role in the causation of cardiovascular diseases. Prevalence of central obesity is high in Nigeria and is associated with increased cardiovascular risk. Aim: To assess the prevalence of central obesity in medical doctors in Bayelsa state using four obesity indices and to determine the association between these indices and compare the ability of these indices to predict cardiovascular risk. Materials and Methods: This was a descriptive crosssectional study conducted between August 2018 and January 2019. Using a structured self-administered questionnaire, data was collected from 244 randomly selected medical doctors. Data included socio-demographic information, work duration and professional cadre, Blood Pressure (BP) was taken. Anthropometric measures which included weight (in Kg), height (in metres), Waist Circumference (WC) and Hip Circumference (HC) in centimeters was taken. From the different measures: Waist-Hip Ratio (WHpR), Waist-Height Ratio (WHtR), Body Mass Index (BMI) was calculated. Based on WHO recommended thresholds, WC, WHpR, WHtR and BMI were used in categorising participants as obese and nonobese. Correlation analysis was done and Receiver Operating Characteristic (ROC) curve was constructed. Statistical significance was set at p-value <0.05. Results: Most doctors in the study were less than 30-year-old (40.2%), married (54.9%) and female doctors made up a third of the respondents (29.9%). The mean age of study participants was 37.4 years (SD-11.3 years) and mean duration of medical practice was 9 years (SD-11.1 years). The prevalence of elevated BP was 26.6% using a BP threshold of ≥140/90 mmHg. The prevalence of obesity was 18.4% using BMI ≥30 kg/m2 . Based on WC, WHtR, and WHpR categorisations, the prevalence of obesity was 44.3%, 58.2%, and 63.1%, respectively. The weakest relationship existed between BMI and BP (r=0.15; p=0.019); while the correlation coefficient (r) between WC and WHtR showed a very strong positive relationship (r=0.88; p=0.001). ROC curve analysis revealed all anthropometric indices obtained modest performances in predicting Cardiovascular Diseases (CVD) risk as indicated by AUC values that were equal to or higher than 0.60. WC performed best in predicting hypertension in study participants (0.69) while BMI was the worst performer (0.60). Conclusion: A high prevalence of central obesity in medical doctors is worrisome given the associated cardiovascular risks. This study shows all four anthropometric indices (WC, WHtR, WHpR and BMI) are useful in predicting cardiovascular risk, with the best and worst predictors being WC and BMI, respectively.